2013
DOI: 10.1073/pnas.1316498110
|View full text |Cite
|
Sign up to set email alerts
|

Frontalin pheromone biosynthesis in the mountain pine beetle, Dendroctonus ponderosae , and the role of isoprenyl diphosphate synthases

Abstract: The mountain pine beetle (Dendroctonus ponderosae Hopkins) is the most destructive pest of western North American pine forests. Adult males produce frontalin, an eight-carbon antiaggregation pheromone, via the mevalonate pathway, as part of several pheromones that initiate and modulate the mass attack of host trees. Frontalin acts as a pheromone, attractant, or kairomone in most Dendroctonus species, other insects, and even elephants. 6-Methylhept-6-en-2-one, a frontalin precursor, is hypothesized to originate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 35 publications
(53 reference statements)
0
31
1
Order By: Relevance
“…It was previously shown that product chain length or activity of plant and insect IDSs can be influenced by heterooligomerization, which may also play a role in (E)-GPP and (Z,E)-FPP synthesis in P. striolata (9,(39)(40)(41). Moreover, IDS product chain length may also be influenced by the IPP/DMAPP ratio (8), and different metal ion cofactors as recently demonstrated in the mustard leaf beetle, Phaedon cochleariae (5). The putative role of PsIDS and PsIDS-like enzymes in the biosynthesis of (Z,E)-FPP are subjects of ongoing research.…”
Section: P Striolata Possesses An Evolutionarily Novel Class Of Tps mentioning
confidence: 93%
See 2 more Smart Citations
“…It was previously shown that product chain length or activity of plant and insect IDSs can be influenced by heterooligomerization, which may also play a role in (E)-GPP and (Z,E)-FPP synthesis in P. striolata (9,(39)(40)(41). Moreover, IDS product chain length may also be influenced by the IPP/DMAPP ratio (8), and different metal ion cofactors as recently demonstrated in the mustard leaf beetle, Phaedon cochleariae (5). The putative role of PsIDS and PsIDS-like enzymes in the biosynthesis of (Z,E)-FPP are subjects of ongoing research.…”
Section: P Striolata Possesses An Evolutionarily Novel Class Of Tps mentioning
confidence: 93%
“…The number of introns per gene ranged from three introns present in genes of P. striolata and T. castaneum to seven introns in the GPPS/FPPS gene of D. ponderosae (8) (Fig. S7).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Another scIDS from Dendroctonus spp. bark beetles produced C 10 -GDP and C 15 -farnesyl diphosphate (C 15 -FDP) depending on the C 5 -IDP/C 5 -DMADP substrate ratio [79][80][81]. Bifunctionality was also observed from the scIDSs characterized from different aphid species [83][84][85][86][87].…”
Section: Iridoid De Novo Synthesis: Early Stepsmentioning
confidence: 99%
“…Strikingly, most of them have the ability to form multiple products. For example, an enzyme studied from the bark beetle, Ips pini, displayed prenyltransferase and terpene synthase activity [79][80][81], resulting in the formation of precursors for the de novo synthesis of monoterpenoid aggregation pheromones such as ipsdienol, which coordinates the colonization of coniferous trees [82]. Another scIDS from Dendroctonus spp.…”
Section: Iridoid De Novo Synthesis: Early Stepsmentioning
confidence: 99%